Labor Allocation Dynamics in Swamp Rice Farming: Influencing Factors and Adaptive Strategies of Farmers - Eka Mulyana (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
Labor allocation is a crucial aspect in the sustainability of rice farming, particularly in lebak swamp areas that possess unique ecological characteristics and demand adaptive strategies from farmers. This study aims to analyze the internal and external factors influencing labor allocation, as well as the strategies adopted by farmers in managing labor within the context of lebak swamp rice farming. A descriptive qualitative approach was employed, with data collected through in-depth interviews involving 30 farmers in Pematang Bangsal Village, Pemulutan Selatan District. The data were analyzed using thematic coding techniques to identify key patterns. The findings reveal that internal factors such as motivation, farming experience, physical health, and farm management significantly affect labor allocation. Meanwhile, external factors include family support, agroecosystem conditions, and access to production inputs. Farmers' adaptive strategies involve intra-household division of labor, the use of hired labor, and adjustment of planting schedules. The study concludes that labor allocation dynamics in lebak swamp rice farming are complex and shaped by the interplay of multiple factors. Therefore, policy interventions and agricultural extension programs must be contextual and sustainable to effectively support labor management in such agroecological settings.